Multi-omics analysis of the regulatory effects of low-phosphorus stress on phosphorus transport in soybean roots - Li, Hongyu; Xu, Letian; Li, Jiaxin; Lyu, Xiaochen; Li, Sha; Wang, Chang; Wang, Xuelai; Ma, Chunmei; Yan, Chao (Frontiers in Plant Science, 2022)
The regulatory effects of uneven phosphorus supplies on phosphorus transport in soybean roots is still unclear. To further analyze the regulatory effects of low-phosphorus stress on phosphorus transport in soybean roots and the effects of uneven phosphorus application on the physiological mechanism of phosphorus transport in soybean roots, dual-root soybean plants were prepared . From the unfolded cotyledon stage to the initial flowering stage, one side of each dual-root soybean system was irrigated with a low-phosphorus-concentration solution, and the other side was irrigated with a phosphorus-free nutrient solution ; this setup allowed the study of the effects of different phosphorus supply levels on the expression of genes and proteins and the accumulation of metabolites in soybean roots on the P- side to clarify the method . The results revealed that the unilateral supply of low-concentration phosphorus promoted the uptake of phosphorus by soybean roots and the transport of phosphorus from the P+ side to the P- side. The low concentration phosphorus supply affected the regulation of the metabolic pathways involved in starch and sucrose metabolism, glycolysis, fructose and mannose metabolism, etc., thereby affecting soybean root phosphorus transport. The low-phosphorus stress inhibited fructose synthesis and sucrose synthase synthesis in the soybean roots and the synthesis of hexokinase (HK) and fructose kinase, which catalyzes the conversion of fructose to fructose-6-phosphate. Low-phosphorus stress promoted the synthesis of sucrose invertase and the conversion of sucrose into maltose by the activity of starch synthase (StS) and stimulated the synthesis of UDPG pyrophosphorylase (UGP) and phosphoglucose isomerase (GP1), which is involved in the conversion of UDP-glucose to glucose-6-phosphate. The phosphorus transport pathway of soybean roots was then affected, which promoted phosphorus allocation to UTP and glucose-6-phosphate. Additionally, low-phosphorus stress hastened glycolysis in the soybean roots and inhibited the synthesis of malic acid, thereby promoting the transport of phosphorus in the roots. In addition, low-phosphorus stress inhibited the synthesis of fructose, mannose, and mannose-1-phosphate and the synthesis of other enzymes involved in phosphorus transport as well as invertase, thereby inhibiting the transport and synthesis of several organic phosphorus-containing compounds.